The Language of Music - Cooke, Deryck (Oxford Oxford University Press, 2001)
First published in 1959, this original study argues that the main characteristic of music is that it expresses and evokes emotion, and that all composers whose music has a tonal basis have used the same, or closely similar, melodic phrases, harmonies, and rhythms to affect the listener in the same ways. He supports this view with hundreds of musical examples, ranging from plainsong to Stravinsky, and contends that music is a language in the specific sense that we can identify idioms and draw up a list of meanings. The book's final section analyzes two symphonies, Mozart's Fortieth and Vaughan Williams's Sixth, to explore the nature of musical inspiration and the process whereby the notes actually convey emotion from composer to listener.
Keywords: Music philosophy and esthetics; Linguistics